Corporate Governance, Karakteristik Dewan Pengawas Syariah dan Maqoshid Sharia Index pada Perbankan Syariah di Indonesia - Ahzar, Fahri Ali; Rosadi, Samsul; Wati, Asiah (AKTSAR: Jurnal Akuntansi Syariah, 2021)
This study aims to examine the effect of corporate governance and the characteristics of the Sharia Supervisory Board on the Maqoshid Sharia Index in Islamic Banking in Indonesia. In this study, corporate governance is proxied by the Board of Directors, Board of Independent Commissioners, Audit Committee, and Institutional Ownership. Meanwhile, characteristics of the DPS are proxied by the size of the DPS, Multiple Positions DPS and the DPS meeting. This study uses research data obtained from the annual reports of Islamic banks in Indonesia in 2015-2019. Technical analysis of data using regression with Common Effects Model after being selected using the Lagrange multiplier test. The study results found that the Independent Board of Commissioners, Institutional Ownership, and Multiple Positions DPS affected the Maqoshid Sharia Index. Meanwhile, the variables of the Board of Directors, the Audit Committee, the size of the DPS, and the DPS meeting have no effect on the Maqoshid Sharia Index in Islamic Banking in Indonesia.Keywords: Corporate governance; Characteristics of the sharia supervisory board; Maqosid Sharia Index; Islamic bank; Indonesia